Penggunaan mata uang kripto pada ekosistem keuangan sosial islam ditinjau dari perspektif pemikiran uang Al-Ghazali: PENGGUNAAN MATA UANG KRIPTO PADA EKOSISTEM KEUANGAN SOSIAL ISLAM DITINJAU DARI PEMIKIRAN UANG AL-GHAZALI - Santoso, Slamet; Janwari, Yadi; Jubaedah, Dedah; Rahmah Kusumah, Nurul; Muharni, Yusraini (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
This research examines the use of cryptocurrency with blockchain in the Islamic social finance ecosystem from Al-Ghazali's point of view on money. Al-Ghazali, one of the great scholars in the Islamic scholarly tradition, has profound thoughts on money, its characteristics, and its uses, which are written in the book Ihya Ulumudin. His thoughts can provide a perspective for analyzing the use of cryptocurrency in various economic aspects, including Islamic social finance. The blockchain opens opportunities for inclusive financial solutions and more equitable access to economic resources. This study used a qualitative approach by reviewing the literature to explore how cryptocurrencies from blockchain technology, especially stablecoins, can support the Islamic social finance ecosystem and align with Al-Ghazali's thoughts. From the study conducted, generally, cryptocurrencies in their function as a medium of exchange and unit of account, their benefits for financial inclusion, wealth distribution, and non-usurious aspects align with Al-Ghazali's thoughts on money. What remains a concern is the use of cryptocurrencies which is still not legally recognized by Bank Indonesia regulations and the fatwa from the Indonesian Ulema Council (MUI) that prohibits it